2020
DOI: 10.1073/pnas.1912307117
|View full text |Cite
|
Sign up to set email alerts
|

Robust hepatitis E virus infection and transcriptional response in human hepatocytes

Abstract: Hepatitis E virus (HEV) is the causative agent of hepatitis E in humans and the leading cause for acute viral hepatitis worldwide. The virus is classified as a member of the genus Orthohepevirus A within the Hepeviridae family. Due to the absence of a robust cell culture model for HEV infection, the analysis of the viral life cycle, the development of effective antivirals and a vaccine is severely limited. In this study, we established a protocol based on the HEV genotype 3 p6 (Kernow C-1) and the human hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 40 publications
7
108
0
Order By: Relevance
“…Furthermore, a single nucleotide exchange leading to a unique restriction site could be successfully introduced into the recombinant virus genome. This demonstrates the suitability of the system for site-directed mutagenesis, which might be used in future studies for investigating the effect of single nucleotide mutations on viral fitness, e.g., mutation G1634R, which has been described to increase the replication efficiency in other HEV strains [22,23].…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, a single nucleotide exchange leading to a unique restriction site could be successfully introduced into the recombinant virus genome. This demonstrates the suitability of the system for site-directed mutagenesis, which might be used in future studies for investigating the effect of single nucleotide mutations on viral fitness, e.g., mutation G1634R, which has been described to increase the replication efficiency in other HEV strains [22,23].…”
Section: Discussionmentioning
confidence: 83%
“…The most commonly used are the Sar-55-related genotype 1 clone [ 68 ], the genotype 3a and 3c Kernow-C1- [ 69 ], and 47832-related [ 70 ] clones, respectively, both of which contain insertions in the HVR, and the genotype 4 TW6196 clone [ 71 ]. A recent presentation of a novel in vitro method to produce high viral titers, allowing study of the full HEV replication cycle in cell culture, has additionally created confidence that we may overcome our limited understanding of HEV pathophysiology [ 72 ]. Although these systems are most commonly used in conventional cell culture systems, several animal infection models have been developed.…”
Section: Virologymentioning
confidence: 99%
“…These differences in the requirement for RIG-I, MDA-5, and MAVS could be due to the use of different cell lines. The host response of primary human hepatocytes (PHHs) to an HEV3–Kernow infection revealed the intrinsic expression of the pattern recognition receptors RIG-I, MDA-5, and TLR3, as well as downstream signaling molecules, including Myd88 and MAVS, showing that this model can trigger an innate immune signaling cascade [ 58 ]. The level of IRF7 mRNA in the livers of rhesus macaques was increased at the peak of HEV1-Sar55 infection [ 50 ], but was reduced when the same monkeys were re-infected [ 59 ].…”
Section: Hev Rna Sensing By Infected Cellsmentioning
confidence: 99%
“…Infecting HepG2 cells and PHHs with the same strain confirmed the increases in type III IFNs λ1 and λ2/3 at the mRNA and protein levels, but not those of type I IFNs [ 56 ]. Lastly, gene ontology enrichment analyses of the biological processes of infected PHHs showed that the IFN signaling pathway was among those with the highest ratio of significantly differentially regulated genes [ 58 ]. These results are in line with the microarray analyses of the chimpanzees’ liver response to an HEV1–Sar55 infection [ 65 ].…”
Section: Innate Immune Response To Hevmentioning
confidence: 99%
See 1 more Smart Citation